Single cell analysis of transcriptome and open chromatin reveals the dynamics of hair follicle stem cell aging - Zhang, Chi; Wang, Dongmei; Dowell, Robin; Yi, Rui (Frontiers in Aging, 2023)
Aging is defined as the functional decline of tissues and organisms, leading to many human conditions, such as cancer, neurodegenerative diseases, and hair loss. Although stem cell exhaustion is widely recognized as a hallmark of aging, our understanding of cell state changes – specifically, the dynamics of the transcriptome and open chromatin landscape, and their relationship with aging - remains incomplete. Here we present a longitudinal, single-cell atlas of the transcriptome and open chromatin landscape for epithelia cells of the skin across various hair cycle stages and ages in mice. Our findings reveal fluctuating hair follicle stem cell (HF-SC) states, some of which are associated with the progression of the hair cycle during aging. Conversely, inner bulge niche cells display a more linear progression, seemingly less affected by the hair cycle. Further analysis of the open chromatin landscape, determined by single-cell Assay for Transposase-Accessible Chromatin (ATAC) sequencing, demonstrates that reduced open chromatin regions in HF-SCs are associated with differentiation, whereas gained open chromatin regions in HF-SCs are linked to the transcriptional control of quiescence. These findings enhance our understanding of the transcriptional dynamics in HF-SC aging and lay the molecular groundwork for investigating and potentially reversing the aging process in future experimental studies.